The Effect of Body Weight on Eating Behavior and Risk for Diabetes, Health Literacy among Turkish Adults: Effect of Body Weight on Eating Behavior - Ulas Kadioglu, Bircan; Soylar, Pınar (Progress in Nutrition, 2021)
Objective This study was aimed to investigate the effect of body weight on eating behavior, risk for diabetes and health literacy of individuals in a primary healthcare center. Design Body weight, eating behavior, risk for diabetes and health literacy level were evaluated in this cross-sectional descriptive study. A total of 210 individuals with normal weight (BMI of 18.5 to <25), overweight (BMI of 25 to <30 kg/m2) and obese (BMI ≥30 kg/m2) were included in the study. The three-factor eating questionnaire (TFEQ) was used to investigate the eating behaviors of the participants. Turkish Health Literacy Scale-32 (THLS-32) and FINDRISC Type 2 Diabetes Risk Assessment Form was used. Results A significant relationship was determined the total score of TFEQ scale and body mass index categories. The risk of diabetes was higher in obese individuals. The scores obtained from THLS-32 were lower in obese individuals. The chances of obese individuals being in the high-risk group for diabetes are 8.47 times higher compared to individuals with normal weight. According to the results of multivariate analysis, this risk is 9.92 times. Conclusions It was determined that increased the body weight associated TFEQ scale and the risk for diabetes and also Health Literacy. Weight management practices should be conducted by a multidisciplinary team for individuals in risk group with high BMI in healthcare centers. Keywords Eating behavior; body weight; body mass index; diabetes mellitus; health literacy